1982
DOI: 10.1136/ard.41.5.441
|View full text |Cite
|
Sign up to set email alerts
|

Clinical response to therapy with thymopoietin pentapeptide (TP-5) in rheumatoid arthritis

Abstract: The effect of thymopoietin pentapeptide (TP-5) was evaluated in patients with rheumatoid arthritis (RA). Ninety-two patients were divided into 3 groups, namely, placebo, TP-5 intramuscularly (IM) 1 mg, TP-5 intravenously (IV) 50 mg, and were evaluated for 6 measures of disease activity at the beginning of the study and at 3 and 6 months. No difference was observed between the placebo group and the group treated with TP-5 IM 1 mg. However, in the group treated with TP-5 IV 50 mg a statistically significant impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1982
1982
2000
2000

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…Diese sollen im Folgenden dargestellt werden [19,21,22,23,24,25]. Teilweise wurden die Untersuchungen placebokontrolliert und randomisiert durchgeführt.…”
Section: Kontrollierte Studienunclassified
“…Diese sollen im Folgenden dargestellt werden [19,21,22,23,24,25]. Teilweise wurden die Untersuchungen placebokontrolliert und randomisiert durchgeführt.…”
Section: Kontrollierte Studienunclassified
“…Particularly, since this sub stance has been claimed to have an effect on rheuma toid arthritis in man [37] and to induce suppressor cell function in mice with autohemolytic anemia [22] it might a priori be considered to be of potential thera peutic use in patients with AD. In the study reported herein we show that patients with AD have deficient relative and absolute numbers of T cells with FcIgG and T8 markers and that TP-5 treatment appears to normalize these deficiencies.…”
Section: Introductionmentioning
confidence: 99%